Pemanfaatan dan Pengembangan Ekonomi Berkelanjutan pada Kawasan Keramba PLTA Koto Panjang Sebagai Desa Wisata dan Edutourism - Nugroho, Handi Wilujeng; Hartanto, Dicki (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Indonesia has great potential in the fisheries sector, including cultivating freshwater fish using the floating cage system which is popular in various regions. However, the potential of floating cages, which are known to be effective, has not yet been fully explored, especially in development as an educational tourism destination or edutourism. This research aims to design and develop the Koto Panjang hydropower cage area into an edutourism destination that can improve the economic welfare of the community while introducing ecosystem diversity and sustainable fish cultivation techniques. The method in this research is participatory design to design facilities and management strategies for cage areas, with SWOT analysis to identify strengths, weaknesses, opportunities and threats in its development. The research results show that the cage area at the Koto Panjang PLTA has great potential as an educational tourism destination that prioritizes environmental conservation and empowerment of local communities. The design of this tourist area includes tourist routes that lead to fish farming, feeding and water quality management areas, as well as interactive facilities for visitor education. The SWOT analysis shows that the strength of the Koto Panjang hydropower cage area lies in its natural resource potential, educational support, environmentally friendly technology and community participation. Weaknesses include limited infrastructure and understanding of edutourism. The opportunities lie in educational tourism trends, while the threats include climate fluctuations and ecosystem damage.